Coxiella burnetii Endocarditis in a Child Caused by a New Genotype. Issue 2 (February 2016) - Briggs, Benjamin J.; Raoult, Didier; Hijazi, Ziyad M.; Edouard, Sophie; Angelakis, Emmanouil; Logan, Latania K.
Abstract : Coxiella burnetii endocarditis is a rare diagnosis in children. We present a case of Q fever endocarditis due to a new genotype, MST 54, and review recent literature on Q fever infections in children. Practitioners should consider Q fever in culture-negative endocarditis, particularly in children with congenital heart disease and history of travel or residence in endemic regions.